2014
DOI: 10.1039/c4cy00642a
|View full text |Cite
|
Sign up to set email alerts
|

Deracemisation of benzylisoquinoline alkaloids employing monoamine oxidase variants

Abstract: Deracemisation of benzylisoquinoline alkaloids was performed employing a recently developed variant of monoamine oxidase from Aspergillus niger (MAO-N variant D11).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…In these cases reversal of enantioselectivity relative to the Turner results was not observed. 8 10 , 12b , 22 Relative to LG-I-D11, a higher ee-value (48%) was obtained for amine 6 by deracemization with mutant LG-J-B4. Interestingly, LG-J-B4 showed reversed stereoselectivity for amine 7 compared with LG-I-D11.…”
Section: Resultsmentioning
confidence: 95%
“…In these cases reversal of enantioselectivity relative to the Turner results was not observed. 8 10 , 12b , 22 Relative to LG-I-D11, a higher ee-value (48%) was obtained for amine 6 by deracemization with mutant LG-J-B4. Interestingly, LG-J-B4 showed reversed stereoselectivity for amine 7 compared with LG-I-D11.…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, if high yields of racemic reticuline can be obtained from simple bacteria fermentation, a deracemization method for reticuline and similar benzoisoquinolines can be the next step. A method using stereoselective oxidation by a monoamine oxidase and reduction by ammonia-borane provided over 97% enantiomeric excess of (S)-reticuline [34].…”
Section: Biosynthetic Steps: Enzymes and Genesmentioning
confidence: 99%
“…Then we applied the Turner‐deracemization technique to racemic valine ethyl ester and l ‐valine ethyl ester by using E. coli whole cells of CHAO and its double mutant Y321I/M226T in combination with a nonselective chemical reducing agent (NH 3 ⋅ BH 3 ) at pH 6.5 and 30 °C. The time–course study (Figure ) showed that the reactions of racemic valine ethyl ester and l ‐valine ethyl ester were fast and linear in the first 2 h and resulted in up to 99 and 77 % ee , respectively, for the mutant Y321I/M226T.…”
Section: Methodsmentioning
confidence: 65%